EFFICIENCY OF HEALTH EXPENDITURE IN ORGANIZATION OF ISLAMIC COOPERATION (OIC) COUNTRIES: A DATA ENVELOPMENT ANALYSIS APPROACH - Helwa, Lina Af'ida Fataya; Rima, Hadijah (EP FEB UNS, 2024)
Studies concerning the efficiency of health spending rank among the primary priorities in global policies aimed at enhancing health equity through improved health services and care. This study focuses on countries belonging to the Organization of Islamic Cooperation (OIC) due to their limited access to healthcare, government health spending, and increasing out-of-pocket expenditure. The study aims to measure efficiency scores of healthcare expenditure in OIC member countries. This research is a quantitative study using a Data Envelopment Analysis (DEA) approach. This study using two variables this input and output variables. Input variables are such as total health expenditures, government health expenditures, and out-of-pocket health expenditures per capita PPP current International , while output variables include life expectancy and infant mortality per 1,000 births. All variables are secondary data derived from World Develompment Indicators (WDI) in World Bank. The research sample comprises 50 out of 57 OIC countries during 2004-2018. Results indicate that the average efficiency score of OIC countries from 2004 to 2018 was 0.551. Predominantly, countries in the Middle East demonstrated the highest efficiency scores, with Qatar leading followed by Brunei Darussalam, Kuwait, UAE, and Saudi Arabia, while Egypt recorded the lowest efficiency score. Based on this research, OIC countries are encouraged to diversify government-owned insurance policies, allocate government health expenditures more precisely, reduce the stunting rate among children, protect the health of pregnant women, and promote health investments.